Tingkat Pengetahuan Petani dalam Pengendalian Hama dan Penyakit Tanaman Kakao di Kecamatan Masamba Luwu Utara - Gaffar Aditya; Syafruddin Syafruddin; Alfian Anggra (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Masamba Regency, North Luwu, is one of the largest cocoa-producing centers in South Sulawesi Province. Almost every region has a cocoa plant (Theobroma cacao L.), and it is relatively easy to grow in climatic conditions suitable for cocoa plants, so it is essential to do the right way for pest and disease control aimed at increasing production. This study aims to determine how much knowledge there is about controlling pests and diseases in cocoa plants. Using a quantitative analysis approach, this research was conducted using a survey technique from November to December 2022. Data obtained from interviews and questionnaire-filling results were used to conduct this research. The population used in this study is a group of farmers in Pandak Village and Pongo Villages. The population used as the targets in this study are the Masagena Farmer Group, the Limbong Dewata Farmer Group, and the Rante Sipulung Farmer Group, each of which is the target of this study. The purposive sampling technique used 50 samples per person. The Structural Equation Modeling (SEM) model uses variance-based statistical tests. Smart Partial Least Squares (Smart PLS) software is used for SEM data analysis to show farmers' knowledge level about pest and disease control of cacao plants. Motivation (X1), role of farmer groups (X2), extension (X3), and knowledge (Y) are the variables analyzed in this study. Based on the analysis results, it is known that X1, X2, and X3 affect Y by 40.9%, while other variables not observed in this study affect 45.7%. This indicates that the level of knowledge in controlling pests and diseases in cacao plants in Masamba District, North Luwu, has an influence, although not significant.